The UNESCO Contribution to Safeguarding and Preserving Jordan’s Cultural Heritage - Hayajneh, Hani; Cesaro, Giorgia (Jordan Journal for History and Archaeology, 2022)
UNESCO seeks to build peace through international cooperation in education, sciences, and culture and contributes to the achievement of the Sustainable Development Goals defined in the 2030 Agenda. The present paper explores how UNESCO, the Jordanian government, and the local communities work together in the design and implementation of plans aimed at developing a knowledge-based economy, protecting Jordan’s natural environment and rich cultural heritage, promoting intercultural dialogue and cultural diversity, and in strengthening the institutionalization of culture for development. The present contribution is divided into two parts, the first covers the institutional/legislative framework; financial capacities of Jordanian institutions and describes the activities undertaken by UNESCO over the past years for the preservation of Jordan’s tangible heritage. The section shows UNESCO’s approach towards the conservation of sites from a more resilience-based perspective in an attempt to realize employment opportunities in the heritage sector and heritage as a vehicle for socio-economic resilience and sustainability. The second part of the present paper covers the collaborative efforts by UNESCO and the Jordanian Government in safeguarding Intangible Cultural Heritage (ICH) in the context of the UNESCO 2003 Convention for Safeguarding Intangible Cultural Heritage, including the inscription of ICH elements into the Representative List of the Intangible Cultural Heritage of Humanity, the establishment of certain Jordanian institutions related to ICH safeguarding, and UNESCO’s support for Safeguarding ICH in Jordan on the national and international levels. This includes capacity building, raising awareness on the importance of ICH, managing and supporting projects for drawing community-based inventories of ICH elements in Jordan, and integrating ICH into the Jordanian educational arena. Some recommendations towards safeguarding ICH in Jordan on both the governmental and societal levels are given, e.g., involving museums, enhancing media and information channels, developing educational plans, investmenting in ICH in the sustainable tourism sector, and modifying existing legislation and constitutional provisions to protect ICH and its bearers.